2021
DOI: 10.1186/s12936-021-03754-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota identified from preserved Anopheles

Abstract: Background Mosquito species from the Anopheles gambiae complex and the Anopheles funestus group are dominant African malaria vectors. Mosquito microbiota play vital roles in physiology and vector competence. Recent research has focused on investigating the mosquito microbiota, especially in wild populations. Wild mosquitoes are preserved and transported to a laboratory for analyses. Thus far, microbial characterization post-preservation has been investigated in only Aedes vexans and Culex pipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 132 publications
(105 reference statements)
1
10
0
1
Order By: Relevance
“…atroparvus , the vast majority from the phylum Proteobacteria . Most of the bacterial taxa herein reported have been described as part of the microbiota in culicid mosquitoes ( Dada et al, 2014 ; Muturi et al, 2016 ; Rocha-David et al, 2016 ; Hegde et al, 2018 ; Kang et al, 2020 ) including Anopheles from different geographic regions ( Rani et al, 2009 ; Djadid et al, 2011 ; Wang et al, 2011 ; Boissiere et al, 2012 ; Gimonneau et al, 2014 ; Ngo et al, 2015 ; Bogale et al, 2020 ; Galeano-Castañeda et al, 2020 ; Zoure et al, 2020 ; Feng et al, 2021 ; Silva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…atroparvus , the vast majority from the phylum Proteobacteria . Most of the bacterial taxa herein reported have been described as part of the microbiota in culicid mosquitoes ( Dada et al, 2014 ; Muturi et al, 2016 ; Rocha-David et al, 2016 ; Hegde et al, 2018 ; Kang et al, 2020 ) including Anopheles from different geographic regions ( Rani et al, 2009 ; Djadid et al, 2011 ; Wang et al, 2011 ; Boissiere et al, 2012 ; Gimonneau et al, 2014 ; Ngo et al, 2015 ; Bogale et al, 2020 ; Galeano-Castañeda et al, 2020 ; Zoure et al, 2020 ; Feng et al, 2021 ; Silva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In adult mosquitoes, diverse dietary regimes (e.g., plant sap and nectar or blood) may alter the composition of the microbiota and incorporate diversity into the microbial communities ( Rani et al, 2009 ). In fact, descriptive studies that have characterized the microbiota of several field populations and/or laboratory colonies of culicid mosquitoes have suggested geographical, species, sex, and even individual variation ( Yadav et al, 2015 ; Akorli et al, 2016 ; Muturi et al, 2016 ; Bascuñan et al, 2018 ; Rodriguez-Ruano et al, 2020 ; Saab et al, 2020 ; Tainchum et al, 2020 ; Silva et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…funestus and An. arabiensis , the presence of a number of bacteria even weeks after mosquitoes’ preservation on silica or in RNAlater ® solution ( E Silva et al, 2021 ). The authors found that the midgut of An.…”
Section: The Bacterial Community and Its Associated Bacteriophages In...mentioning
confidence: 99%
“…arabiensis was mainly colonized by Bacteroidetes and Proteobacteria , with the latter being the predominant one colonizing An. funestus midgut ( E Silva et al, 2021 ). Elizabethkingia and Serratia were found in both An.…”
Section: The Bacterial Community and Its Associated Bacteriophages In...mentioning
confidence: 99%
“…Альтернативой криоконсервации для особо ценных образцов могут служить различные коммерческие реагенты, например, Allprotect Tissue Reagent (Qiagen) или RNAlater (Ambion), позволяющие без использования жидкого азота и сухого льда фиксировать ДНК образцов до 1 суток при 37 °C, до 7 суток при комнатной температуре, до 4 недель при 2-8 °C или неограниченно при -20 или -80 °C (Gorokhova, 2005;Nagy, 2010;Peña-Llopis, Brugarolas, 2013;Silva et al, 2021). Важно, что повторная разморозка/ заморозка образца не нарушает сохранность ДНК, однако морфологические структуры могут пострадать.…”
Section: хранение и подготовка материала к экстракции днкunclassified